(untitled) - Pitzer, Kenneth S. (New York, 1995)
This book is to supply quantum theory and statistical mechanics as applied to chemical problems ranging from the potential restricing rotation about single bonds,...
Keywords: Thermodynamics,Chemistry, physical and theoretical